Yielding and its adaptability of several promising bulk cocoa clones (Pelita Perkebunan (a Coffee and Cocoa Research Journal), 2005)
Yielding and its adaptability are considered to be an important criteria for clones recommendation. An experiment to evaluate yield and its adaptability of several promising bulk cocoa clones has been executed during 1996—2003 in three locations having different altitude and type of climate, consisted of Jatirono(450 m asl., B type of climate), Kalisepanjang (275 m asl., C type of climate) and Kalitelepak (145 m asl., B type of climate). Randomized completely block design (RCBD) was used in each location with 14 promising clones and four replications. Recommended clones of ICS 60 and GC 7 were used as standard. The promising clones were originated from mother trees selection with the main criteria of yield. Observations were conducted on yield and its components as well as bean characteristics. Determination of adaptability of each clone by using yield performance and its stability. Statistical analysis was done by using combined analysis. The results showed that KW 30 and KW 48 perform higher yield (2.3 ton/ha) than that of standard clone (1.7 ton/ha) as well as consistant yield stability between location and over years. There for, the two clones performed good adaptability. KW 30 and KW 48 also perform good yield components, and high percentage of fat content i.e 55%. So, those clones are potential to be recommended for commercial planting materials. Key words : bulk cocoa, yield, clone, stability, adaptability.